MORAL AND LEGAL FOUNDATIONS OF INFORMATION SECURITY IN UZBEKISTAN ("Conference on Universal Science Research 2023", 2023)
In this article, we will talk about the loss and alteration of information about what is information security it is said that information is protected on any carriers from accidental and intentional effects of directed natural or artificial nature.